POLITICALAWARENESSAMONGUNDER GRADUATE STUDENTS (International Journal of Food and Nutritional Sciences, 2022)
The 21st century is often referred to as the Knowledge Century. Nowadays, young people dedicate a significant portion of their time to various social media platforms such as WhatsApp, Facebook, and Twitter. It is widely recognized that these platforms have become new sources of information, gradually evolving into a means of acquiring knowledge. Given that India boasts one of the world's youngest populations, this study aims to investigate the level of political awareness among undergraduate students who are approximately 20 years old.